2020
DOI: 10.1016/j.irfa.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The economic importance of rare earth elements volatility forecasts

Abstract: We compare the suitability of short-memory models (ARMA), long-memory models (ARFIMA), and a GARCH model to describe the volatility of rare earth elements (REEs). We find strong support for the existence of long-memory effects. A simple long-memory ARFIMA() baseline model shows generally superior accuracy both in-and out-of-sample, and is robust for various subsamples and estimation windows. Volatility forecasts produced by the baseline model also convey material forward-looking information for companies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…We demonstrated that superdiffusive FBM with large H values is outside the large-deviation bound. Superdiffusive FBM applied in mathematical finance are indeed in this range of H values [58][59][60], and our large-deviation tool is therefore well suited for the analysis of such processes. We also showed that the large-deviation tool is able to uncover subtle correlations in the data, similarly to ARFIMA analyses applied mainly in mathematical finance and time series analysis.…”
Section: Discussionmentioning
confidence: 96%
“…We demonstrated that superdiffusive FBM with large H values is outside the large-deviation bound. Superdiffusive FBM applied in mathematical finance are indeed in this range of H values [58][59][60], and our large-deviation tool is therefore well suited for the analysis of such processes. We also showed that the large-deviation tool is able to uncover subtle correlations in the data, similarly to ARFIMA analyses applied mainly in mathematical finance and time series analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Another aspect that should be considered is the volatility price of metals and rare earths, as vanadium, zinc, and cerio. [35] In other words, significant price variations can have a strong effect of the final price of the batteries making them unfeasible from an economic point of view. Therefore, risk management strategies should also be analyzed for coping with pricing risk.…”
Section: Preliminary Economic Surveymentioning
confidence: 99%
“…Regarding REEs, there are many challenges associated with their extraction and processing and thus their global availability. These include (i) their geological distribution, as it is known that REE-containing minerals rarely occur in concentrated forms, thus making their exploitation difficult and (ii) their presence with uranium or thorium decay chains, which makes their processing more challenging and expensive [56][57][58]. As a result, urban mining will be a pillar of the circular economy in the near future and is anticipated to have strong economic (generating profit through the development and application of innovative technologies), and environmental (reducing environmental impacts) benefits [59].…”
Section: Mine Of the Futurementioning
confidence: 99%